Use of stewardship smartphone applications by physicians and prescribing of antimicrobials in hospitals: A systematic review - Helou, R. I. (PLoS One, 2020)
BACKGROUND: Antimicrobial stewardship (AMS) programs promote appropriate use of antimicrobials and reduce antimicrobial resistance. Technological developments have resulted in smartphone applications (apps) facilitating AMS. Yet, their impact is unclear. OBJECTIVES: Systematically review AMS apps and their impact on prescribing by physicians treating in-hospital patients. DATA SOURCES: EMBASE, MEDLINE (Ovid), Cochrane Central, Web of Science and Google Scholar. STUDY ELIGIBILITY CRITERIA: Studies focusing on smartphone or tablet apps and antimicrobial therapy published from January 2008 until February 28th 2019 were included. PARTICIPANTS: Physicians treating in-hospital patients. INTERVENTIONS: AMS apps METHODS: Systematic review. RESULTS: Thirteen studies met the eligibility criteria. None was a randomized controlled trial. Methodological study quality was considered low to moderate in all but three qualitative studies. The primary outcomes were process indicators, adherence to guidelines and user experience. Guidelines were more frequently accessed by app (53.0% - 89.6%) than by desktop in three studies. Adherence to guidelines increased (6.5% - 74.0%) significantly for several indications after app implementation in four studies. Most users considered app use easy (77.4%—>90.0%) and useful (71.0%—>90%) in three studies and preferred it over guideline access by web viewer or booklet in two studies. However, some physicians regarded app use adjacent to colleagues or patients unprofessional in three qualitative studies. Susceptibility to several antimicrobials changed significantly post-intervention (from 5% decrease to 10% - 14% increase) in one study. CONCLUSIONS: Use of AMS apps seems to promote access to and knowledge of antimicrobial prescribing policy, and increase adherence to guidelines in hospitals. However, this has been assessed in a limited number of studies and for specific indications. Good quality studies are necessary to properly assess the impact of AMS apps on antimicrobial prescribing. To improve adherence to antimicrobial guidelines, use of AMS apps could be considered.